Adaptative Skills and Global Functioning of Unaccompanied Migrant Minors in Europe: A Systematised Review - Dimitri Prod'hom; Dimitri Prod'hom; Joëlle Rosselet Amoussou; Kerstin Jessica Plessen; Kerstin Jessica Plessen; Noémie Cuissart de Grelle; Sydney Gaultier; Sydney Gaultier (Frontiers Media S.A., 2024)
ObjectivesThis systematised review aimed to examine European literature reporting data about adaptative skills and global external functioning of unaccompanied minors (UAMs).MethodsWe conducted a systematised screening of four databases (APA PsycINFO Ovid, Medline Ovid ALL, Embase.com and Web Of Science Core Collection) using a research strategy including social, scholarly and behavioural abilities as well as externalising problems associated with the target population of UAMs. Thirty articles were included using pre-defined inclusion and exclusion criteria.ResultsOur review showed that despite high levels of internalising disorders, socio-behavioural and educational adjustment of UAMs remained positive. It demonstrated how this population displays a strong desire for academic success and prosocial behaviours instead of aggressivity in everyday life. Nevertheless, our review drew attention to the strong tendency of UAMs to internalise their disorders and display chronic distress and problematic behaviours which increased with time spent in the host country.ConclusionOur study draws attention to the risk of underestimating the real mental health needs of refugees, due to preserved external functioning combined with significant settlement pressures.